Bauxite residue (red mud) as a pulverised fuel ash substitute in the manufacture of lightweight aggregate. (20th January 2016) - Molineux, Chloe J.; Newport, Darryl J.; Ayati, Bamdad; Wang, Chuang; Connop, Stuart P.; Green, Jon E.
Abstract: This study looked at the potential of bauxite residue or red mud to be used in the manufacture of lightweight aggregate in replacement of pulverised fuel ash (PFA), commonly used as a way of recycling problematic wastes. The percentage replacements of red mud with PFA were as follows: 25, 31, 38, 44 and 50%. These were blended in a mix with waste excavated clay and sewage sludge – all from the Chongqing municipality in China. Lightweight pellets were produced using a Trefoil rotary kiln and were sintered to 1200 °C. Results showed that 44% bauxite residue replacement produced lightweight pellets with the highest compressive strength, highest density and largest water holding capacity. This would be expected in materials with a low level of silicates, which causes insufficient glass phase viscosity and therefore poor bloating during firing; producing an aggregate with a higher density but with open pores that allowed for larger water absorption. All ratios of red mud aggregates were significantly reduced in pH after firing to around pH 8, and this reduced the leachability of the aggregates to levels below those set by the European landfill directive (2003/33/EC). Highlights: We successfully manufactured lightweight aggregate using bauxite residue (red mud). 44% red mud replacement is most successful for strength and water holding capacity. 44% also produced highest density due to insufficient glass phase viscosity. All ratios significantly reduced in pH after firing to around pH 8. Leachability of all aggregates below levels set by European landfill directive (2003/33/EC).